2022
DOI: 10.1039/d2cc00334a
|View full text |Cite
|
Sign up to set email alerts
|

The back-deposition of dissolved Mn2+ to MnO2 cathodes for stable cycling in aqueous zinc batteries

Abstract: The back-deposition of dissolved Mn2+ is a key factor for stable cycling of MnO2 cathodes in aqueous zinc batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…This demonstrates that the C@MnSe@GO-2 cathode is capable of inducing the in situ oxidation of Mn 2+ to generate multivalent manganese-based oxides on its surface during battery charging, which is consistent with previous reports. 38,49,50 After discharging the electrode completely, characteristic peaks of Zn 2 MnO 4 (29.92°, 34.48°), MnOOH (33.48°, 38.96°) and Zn 4 (OH) 6 SO 4 · x H 2 O (ZSH, 25.28°, 25.52°, 32.56°, 35.40°, and 35.76°) can be observed at the electrode, which are the same as those of the characteristic discharge products of manganese-based oxides produced in AZIBs. 51 The C@MnSe@GO-2 electrode was tested by ex situ Raman spectroscopy, as shown in Fig.…”
Section: Resultsmentioning
confidence: 63%
“…This demonstrates that the C@MnSe@GO-2 cathode is capable of inducing the in situ oxidation of Mn 2+ to generate multivalent manganese-based oxides on its surface during battery charging, which is consistent with previous reports. 38,49,50 After discharging the electrode completely, characteristic peaks of Zn 2 MnO 4 (29.92°, 34.48°), MnOOH (33.48°, 38.96°) and Zn 4 (OH) 6 SO 4 · x H 2 O (ZSH, 25.28°, 25.52°, 32.56°, 35.40°, and 35.76°) can be observed at the electrode, which are the same as those of the characteristic discharge products of manganese-based oxides produced in AZIBs. 51 The C@MnSe@GO-2 electrode was tested by ex situ Raman spectroscopy, as shown in Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Before reviewing the MnO 2 /Mn 2+ -chemistry-inspired energy storage devices in detail, the mechanistical or historical aspects of MOR/MRR must be understood (Soundharrajan et al, 2022a). Although several reports regarding modern-day battery devices inspired by MnO 2 /Mn 2+ chemistry have been published recently (Moon et al, 2021;Zheng et al, 2021;Liu et al, 2022a;Yang et al, 2022;Naresh et al, 2023;Ye et al, 2023), the observation of unique MnO 2 /Mn 2+ chemistry was first reported in 1998 in relation to the Zn/ZnSO 4 /MnO 2 rechargeable cell by Kim et al (Kim and Oh, 1998). Although the Zn/ZnSO 4 /MnO 2 rechargeable cell was not coined as ZIBs by Kim et al (Kim and Oh, 1998), the use of mildaqueous ZnSO 4 electrolyte for Zn/MnO 2 rechargeable cells could termed as ZIBs, as per the recent nomenclature.…”
Section: Overview Of the Evolutions Of Aqueous Rechargeable Batteriesmentioning
confidence: 99%